Changes in temperature of newborn babies bathed immediately after birth (Faculty of Medicine Universitas Indonesia, 2003)
In the tropics, bathing full-term newborn babies are routinely done immediately after birth, although it is usually not recommended until 2 - 6 hours of age. Yet, there is no study in Indonesia about hypothermia in newborns bathed immediately after birth. The aim of this study is to determine the influence of bathing the newborn immediately after birth to the body temperature and hypothermia. One hundred and twenty five healthy full-term newborn babies delivered on March 1999 were included and separated into two groups, 59 newborns were bathed immediately after birth and 66 newborns were bathed later. There was no statistical difference between both groups in the mean of birth weight, gestational age, room temperatures, gender, delivery method, and risk of infection. Mean body temperature between both groups were not statistically different on the 0 and the 30th minute after birth. On the other hand, on the 15th minute after birth, the mean body temperature of the immediately bathed group was statistically lower than not immediately bathed group [36.84 (SD 0.25)°C vs 37.02 (SD 0.27)°C, p=0.0001]. On the 15th minute after birth, there were four (6.8%) hypothermic babies (rectal temperature < 36.5°C) in the immediately bathed group and one (1.5%) hypothermic baby in the not immediately bathed group (p=0.134). Conclusion, bathing healthy full-term newborn babies immediately after birth will decrease the body temperature, but hypothermia occurred only in very small numbers which are not statistically significant. (Med J Indones 2003; 12: 73-79) Keywords: hypothermia, newborn baby, bathed immediately after birth